1986
DOI: 10.1038/bjc.1986.134
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo malignant transformation of mouse fibroblasts in the presence of human tumour xenografts

Abstract: Summary During the routine serial passage of over 30 human tumour xenografts in athymic (nu. nu.) mice over a period of 6 years the induction of murine fibrosarcomas at the site of transplantation has been observed on three occasions. In two cases it has been possible to follow the development of these tumours over successive transplant generations. These sarcomas had growth rates, tumour karyotypes and isoenzyme patterns which clearly distinguished them from the original human xenografts.Human tumour xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Although there was no evidence for metastatic spread in the experiments reported herein this may have been due to the rapid growth of the primary tumours which necessitated the termination of experiments before the tumours ulcerated. Our findings concerning the rapid growth of these tumours are in agreement with those of Sparrow et al (1986) who pointed out that since human tumour xenografts grow relatively slowly, rapid tumour growth and skin ulceration should alert the investigator of possible malignant transformation of endogenous murine cells. The incidence of 'T' lymphomas in our system (5/6) is much higher than that reported by other workers.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Although there was no evidence for metastatic spread in the experiments reported herein this may have been due to the rapid growth of the primary tumours which necessitated the termination of experiments before the tumours ulcerated. Our findings concerning the rapid growth of these tumours are in agreement with those of Sparrow et al (1986) who pointed out that since human tumour xenografts grow relatively slowly, rapid tumour growth and skin ulceration should alert the investigator of possible malignant transformation of endogenous murine cells. The incidence of 'T' lymphomas in our system (5/6) is much higher than that reported by other workers.…”
supporting
confidence: 81%
“…The incidence of 'T' lymphomas in our system (5/6) is much higher than that reported by other workers. Sparrow et al (1986) reported 3 murine fibrosarcomas which arose over a 6 year period from 30 human xenografts. In this respect the RPMI-8226 cell line appears more effective in initiating the production of endogenous virus which results in lynmphoma production than they are of becoming established as a xenograft.…”
mentioning
confidence: 99%
“…Occasionally, the induction of murine tumors following human tumor transplantation has been observed [61,120]. These s.c. tumors were invasive, penetrating both the muscularis and the epidermis [120].…”
Section: Maintenance Of Characteristicsmentioning
confidence: 99%
“…These stromal cells are considered normal and never undergo malignant transformation (2,(25)(26)(27). However, the malignant transformation of the tumor stromal cells, particularly CAFs and their origin, MSCs, in vitro and in vivo has been previously reported (28)(29)(30)(31)(32)(33)(34). Therefore, this remains a controversial topic that requires further investigation.…”
Section: Introductionmentioning
confidence: 99%